Psychological well-being and resilience in pedagogical higher education students - Estrada Araoz, Edwin Gustavo (2020)
The objective of this research was to determine the relation between psychological well-being and resilience in students of the Institute of Public Pedagogical Higher Education “Nuestra Señora del Rosario” in the city of Puerto Maldonado, 2019. The research approach was quantitative, the design was not experimental and correlational level. The sample was made up of 134 students and was determined by a stratified probabilistic sampling, the data collection instruments were: the Sánchez Cánovas Psychological Welfare Scale and the Wagnild and Young Resilience Scale (ER). The results determined that psychological well-being was directly and significantly related to resilience since Spearman's rho correlation coefficient was 0.702 with a p-value below the level of significance (p = 0.000 <0.05). Finally, it is concluded that as long as the students have adequate psychological well-being, their resilience will be greater and vice versa.